Monthly Bookkeeping Report System Website Based Waterfall Method On Vinny Kitchen MDO Shop - Rumondor, Aaron; Rosita, Ai (STIKOM Tunas Bangsa Pematangsiantar, 2024)
The Vinny Kitchen Mdo company is a private, family-owned business which is engaged in the production of bread and various types of cakes. This business was developed by the owner herself and operates independently so that the available systems are still in conventional or manual form. One example is a cashier system that still uses manual calculations using a calculator. Transaction calculations that are still manual often experience errors in goods data collection and monthly income calculations. Therefore, it is hoped that the design of the cashier application can help the admin or cashier process to provide services automatically to customers or shop owners so that it does not take time to calculate income or stock manually. This system is also capable of presenting monthly reports in the shop so that they can be recorded. The method used in this system is the Waterfall Method, namely a systematic and sequential process model so that it can be designed in a structured manner. This cashier system was created using a web-based application model, making it easy for admins and cashiers to calculate sales and availability of goods automatically.